La bienveillance : une compétence socio-émotionnelle de l'enseignant au service du bien-être et des apprentissages ? - Rebecca Shankland; Nicolas Bressoud; Damien Tessier; Philippe Gay (Université de Provence, 2018)
Is kindness useful in classroom contexts? This article proposes an operational definition of kindness in school contexts and presents a synthesis of research studies showing its beneficial effects on well-being at school and on learning. Research studies have shown that negative emotions can have negative effects on memory, attention, creativity, motivation to learn and psychosocial functioning. Conversely, positive emotions can enhance learning in classrooms as well as well-being and relationship quality. Studies have also shown that training teachers to modify their interactional style in order to better respond to students' basic psychological needs leads to higher levels of teacher and student well-being and better school performance. Kindness in school contexts can thus be considered as having positive effects on students' and teachers' work. This encourages further research into this field.